Medication Exposure in Highly Adherent Psychiatry Patients - Sutherland, Jeffrey J; Daly, Thomas M; Jacobs, Karen; Khawam, Elias A; Pozuelo, Leo; Morrison, Ryan D; Milne, Stephen B; Daniels, J. Scott; Ryan, Timothy P (ACS chemical neuroscience, 2018)
Medication exposure is dependent upon many factors, the single most important being if the patient took the prescribed medication as indicated. To assess medication exposure for psychotropic and other medication classes, we enrolled 115 highly adherent psychiatry patients prescribed five or more medications. In these patients, we measured 21 psychotropic and 38 nonpsychotropic medications comprising a 59 medication multiplex assay panel. Strict enrollment criteria and reconciliation of the electronic health record medication list prior to study initiation produced a patient cohort that was adherent with 91% of their prescribed medications as determined by comparing medications detected empirically in blood to the electronic health record medication list. In addition, 13% of detected medications were not in the electronic health record medication list. We found that only 53% of detected medications were within the literature-derived reference range with 41% below and 6% above the reference range specific to each medication. When psychotropic medications were analyzed near trough-level, only sertraline was found to be within the literature-derived reference range for all patients tested. Concentrations of the remaining medications indicated extensive exposure below the reference range. This is the first study to empirically and comprehensively assess medication exposure obtained in comorbid polypharmacy patients, minimizing the important behavioral factor of adherence in the study of medication exposure. These data indicate that low medication exposure is extensive and must be considered when therapeutic issues arise, including the lack of response to medication therapy.